In Vitro Pollen Viability, Fluorescence Microscopy, and Transcriptomic Comparison of Self-Pollinated and Cross-Pollinated Inflorescence of Artemisia annua L. to Analyze Candidate Self-Incompatibility-Associated Genes - Yimei Zang; Shengrong Cui; Shugen Wei; Limei Pan; Lingyun Wan; Xiaojun Ma; Zuliang Luo; Jine Fu; Chongnan Wang (Horticulturae, 2025)
Artemisia annua L., the primary source of the antimalarial compound artemisinin, is of great importance for malaria treatment. However, its self-incompatibility (SI) restricts selfing breeding and results in unstable artemisinin content which is vulnerable to environmental fluctuations. To address this, our study employed fluorescence microscopy and transcriptomic analysis on stigmas post self- and cross-pollination to explore the molecular mechanisms of SI in Artemisia annua L. Fluorescence microscopy observations indicate that, three hours after pollination, cross-pollinated pollen tubes mostly exhibit normal filamentous growth, whereas the growth of self-pollinated pollen tubes is significantly inhibited, with most appearing as growth-arrested pollen tubes. Using transcriptome analysis, we generated approximately 25.03 GB of data assembled into 69,498 genes and identified 620 differentially expressed genes (DEGs), including 10 classified as SI response genes. Several specific SI-related candidate genes were identified, such as the S-locus receptor kinase (SRK), Calmodulin-like (CML), modifier (MOD), and exocyst complex component (EXO) genes, between AasB and AahA. These DEGs provide vital information for studying A. annua’s SI molecular mechanisms. The putative DEGs between the two groups provided important information for a further study of the molecular mechanisms of SI in A. annua. Candidate SI-associated genes are essential for the genetic engineering of A. annua to overcome SI and to avoid breeding inbred lines.